Development of Visibly Opaque Polyolefin Sheets While Preserving Infrared-Light Transparency - Md. Saiful Hoque; Mehnab Ali; Xiaoruo Sun; Asad Asad; Patricia I. Dolez; James David Hogan; Dan Sameoto (Micromachines)
This study focused on developing pigmented linear low-density polyethylene (LLDPE) sheets while preserving their mechanical properties and infrared (IR) transparency. Six pigments—ZnO, ZnS, TiO2, FeO yellow, FeO light brown, and FeO dark brown—were each mixed with polyethylene (PE) wax in a 1:1 ratio and blended with LLDPE at concentrations of 1, 3, and 5 wt%. Tensile strength tests showed minimal changes at lower pigment concentrations, with values near that of pure LLDPE (14 MPa), and slight reductions at 5 wt%. IR transparency tests, conducted using both direct and reflected heat sources, showed that white-pigmented sheets maintained over 85% transparency, while colored pigments exhibited slightly reduced IR transmittance, ranging from 70% to 91%. Fourier Transform Infrared Spectroscopy (FTIR) analysis confirmed that the critical IR transparency range of 8–12 μm remained unaffected with both pure and pigmented sheets. On the other hand, ultraviolet–visible (UV–VIS) testing showed that white-pigmented sheets experienced enhanced visible-light absorption with increasing pigment concentration and thickness, while color-pigmented sheets exhibited high opacity. Additionally, micro-structuring was performed on the LLDPE sheets to further modify their IR properties, which resulted in effective scattering of IR radiation. These findings highlight the potential of pigmented LLDPE sheets for applications requiring both visual opacity and IR transparency, such as thermal management and camouflage, as well as applications requiring tunable IR properties.